Hyperpolarized 13C Magnetic Resonance Spectroscopy Reveals the Rate-Limiting Role of the Blood–Brain Barrier in the Cerebral Uptake and Metabolism of l‑Lactate in Vivo - Takado, Yuhei; Cheng, Tian; Bastiaansen, Jessica A. M; Yoshihara, Hikari A. I; Lanz, Bernard; Mishkovsky, Mor; Lengacher, Sylvain; Comment, Arnaud (ACS Chemical Neuroscience, 2018)
The dynamics of l-lactate transport across the blood–brain barrier (BBB) and its cerebral metabolism are still subject to debate. We studied lactate uptake and intracellular metabolism in the mouse brain using hyperpolarized 13C magnetic resonance spectroscopy (MRS). Following the intravenous injection of hyperpolarized [1-13C]lactate, we observed that the distribution of the 13C label between lactate and pyruvate, which has been shown to be representative of their pool size ratio, is different in NMRI and C57BL/6 mice, the latter exhibiting a higher level of cerebral lactate dehydrogenase A (Ldha) expression. On the basis of this observation, and an additional set of experiments showing that the cerebral conversion of [1-13C]lactate to [1-13C]pyruvate increases after exposing the brain to ultrasound irradiation that reversibly opens the BBB, we concluded that lactate transport is rate-limited by the BBB, with a 30% increase in lactate uptake after its disruption. It was also deduced from these results that hyperpolarized 13C MRS can be used to detect a variation in cerebral lactate uptake of <40 nmol in a healthy brain during an in vivo experiment lasting only 75 s, opening new opportunities to study the role of lactate in brain metabolism.